The Education of Children in Amoris Laetitia in Light of Thomist Philosophy - RODRIGO BULBOA (Ignatianum University Press, 2021)
This article deals with the essentially human and personal meaning of education presented to us by Pope Francis' Apostolic Exhortation Amoris Laetitia. This work is carried out because of the "Family Year" established to be celebrated from March 2021 to June 2022. It is intended to show that the Exhortation is a true response to the "educational emergency" denounced by Pope Benedict XVI since 2008. A study of chapter VII of the above-mentioned letter, entitled "Towards a better education of children", analyzes and compares with the philosophical principles universally recognized in history about education, especially in St. Thomas Aquinas, with regard to the moral formation of children, recognizing the significant and fundamental responsibility of parents in this important matter. At the end of the analysis it is concluded that the magisterial text is rooted in the tradition of Christian philosophical thought and that, as such, it collaborates, as a light and guide, in the educational work of parents and, therefore, in providing solutions to the problems facing education today; but with regard to the philosophy of the Thomistic being, we cannot say that there is a basis in this metaphysics, although it is perfectly complementary. Este artículo se ocupa del significado esencialmente humano y personal de la educación que nos presenta la Exhortación Apostólica Amoris Laetitia del Papa Francisco. Se realiza este trabajo en razón del "Año de la Familia" establecido para celebrarse desde marzo de 2021 a junio de 2022. Verdadera respuesta a la "emergencia educativa" denunciada a partir de enero de 2008 en el Mensaje del Santo Padre Benedicto XVI a la Diócesis de Roma. Mediante un estudio del capítulo VII de la mencionada carta (Papa Juan Pablo II, 1998), denominado "Fortalecer la educación de los hijos", se analiza y compara con los principios filosóficos universalmente reconocidos en la historia acerca de la educación, especialmente en Santo Tomás de Aquino, en lo que se refiere a la formación moral de los hijos, reconociendo la significativa y fundamental responsabilidad de los padres en esta importante materia. Al finalizar el análisis se concluye que el texto magisterial está enraizado en la tradición del pensamiento filosófico cristiano y que, como tal, colabora, como luz y guía, en la labor educativa de los padres y, por tanto, en dar solución a los problemas que enfrenta la educación hoy en día; pero respecto de la filosofía del ser tomista, no podemos decir que exista un fundamento en esta metafísica, aunque es perfectamente complementaria (Pontificia Academia Sancti Thomae Aquinatis, 2010).